Field test and electrode optimization of electrodynamic cleaning systems for solar panels. (13th September 2019) - Faes, Antonin; Petri, Delphine; Champliaud, Jonathan; Geissbühler, Jonas; Badel, Nicolas; Levrat, Jacques; Roustom, Bahaa; Hessler‐Wyser, Aïcha; Wyrsch, Nicolas; Ballif, Christophe; Getaz, Guy‐Olivier; McKarris, George; et al.
Abstract: Soiling is the major cause of power loss of photovoltaics (PV) and concentrated solar power (CSP) in desert areas. Electrodynamic cleaning system (EDS) is an automatic and water‐free integrated cleaning system for mirrors or solar panels, which uses pulsed electric fields to remove dust off their surface. The first EDS field test over a long period on PV modules is reported here and shows a clear effect on soiling reduction in real conditions in Saudi Arabia. A total of 458 days of measurements is analyzed, and depending on the considered periods, performance losses due to soiling (soiling rate) can vary from −0.06%/day to −0.41%/day for a reference module, while the relative soiling rate reduction using an EDS can be up to 95.7% with an average of 32.1%. Cost calculations demonstrate an added value of the modules equipped with the EDS between 2.6 and 5.2 ¢/Wp compared with usual cleaning system, which is nearly between 10% and 20% of the module price. In addition, extended indoor tests of various electrode designs of EDS for heliostat dedicated to CSP or PV applications show a high cleaning efficiency of up to 98% with front glass thickness of more than 1 mm. A good specular reflectivity, only 4% lower than the bare reference mirror, is obtained with patterned sputtered silver in a spiral electrode design. High reliability of two types of electrode deposition is demonstrated after 200 cycles between −40°C and +85°C. Abstract : The first field test over a long period of electrodynamic cleaning system (EDS) on the PV module shows a clear effect on soiling reduction in Saudi Arabia. The total of 458 days of measurement is separated in six periods, during which performance loss due to soiling (soiling rate) can vary from −0.06%/day to −0.41%/day for a reference module. Over one period, EDS avoids nearly all soiling with only −0.003%/day of soiling rate.